Autonomy concerns with using contracts to enhance patient adherence. (22nd April 2022) - Strassle, Camila Losada; Schwan, Ben; Berkman, Benjamin E.
Abstract: The failure of many patients with chronic conditions to correctly follow medical advice that they hope or intend to follow is a major concern, especially as effective long‐term therapies for chronic conditions materialize. Some US healthcare providers have responded with strategies that involve implementing contracts with their patients, including provisions that may deny future treatments after continued nonadherence. This is among the first articles to explicitly discuss the ethics of patient contracts.